Economics of climate change mitigation in Central and West Asia. (South Asia working papers., 2017)
The ecological complexity of the Central and West Asian region gives way to diverse ecosystems with rich natural resources and hydrocarbon reserves; countries in this region are not only exposed to climate change risks, but there is growing recognition that their carbon-intensive economies necessitate reduction in GHG emissions in line with global efforts to mitigate climate change.